Pengaruh Metode Bermain Peran Terhadap Kemandirian Anak Prasekolah di TK Negeri Pembina Kecamatan Trimurjo Lampung Tengah - Prima Dian Furqoni; Rudi Winarno (MAHESA : Malahayati Health Student Journal, 2021)
ABSTRACT: EFFECT OF ROLE PLAYING METHOD ON PAUD CHILDREN'S INDEPENDENCE IN BUYER STATE Kindergarten, TRIMURJO DISTRICT, LAMPUNG CENTRAL Introduction: The independence of preschool-aged children is a developmental stage that must be carried out by preschool-aged children in accordance with developmental tasks that are appropriate for their age. However, not all children are able to pass developmental tasks optimally. One way to optimize the independence of preschool children is to use the method that children prefer, namely the role-playing method. Objective: This study was to determine the effect of the role-playing method on the independence of preschool children.Methods: The study was conducted on May 14-26 using observation sheets. The population in this study was TK Negeri Pembina students totaling 120 students. The number of samples was 60 students, 30 people as the control group and 30 people as the intervention group. The research method used is a quasi-experimental approach with a pre-post-test control group approach and uses t-test analysis (paired t-test) to measure the independence of preschool children before and after the role-playing method and independent t-test to see the difference between the interventions. and control group.Results: From statistical tests, it is known that there is an effect of the role-playing method on the independence of preschool children in Pembina State Kindergarten, Trimurjo District, Central Lampung in 2012 with a P-Value of 0.000 with a confidence level of 0.05 so that P-Value < (0.000 < 0.05).Conclusion: These results can apply the role-playing method with the design of activity plans that children like and are interested in. Keywords: Role Playing Method and PAUD Children's Independence  INTISARI: PENGARUH METODE BERMAIN PERAN TERHADAP KEMANDIRIAN ANAK PRASEKOLAH DI TK NEGERI PEMBINA KECAMATAN TRIMURJO LAMPUNG TENGAH Pendahuluan: Kemandirian bagi anak usia prasekolah adalah suatu tahapan perkembangan yang harus mampu untuk dilakukan anak usia prasekolah sesuai dengan tugas perkembangan sesuai usia. Akan tetapi, tidak semua anak mampu melewati tugas perkembangan secara optimal. Salah satu cara mengoptimalkan kemandirian anak prasekolah adalah dengan sebuah metode yang disukai anak yaitu metode bermain peran. Tujuan: penelitian ini untuk mengetahui pengaruh metode bermain peran terhadap kemandirian anak prasekolah.Metode: Penelitian dilaksanakan pada tanggal 14-26 Mei dengan menggunakan lembar observasi.P opulasi dalam penelitian ini adalah siswa-siswi TK Negeri Pembina yang berjumlah 120 siswa. Jumlah sampel 60 siswa, 30 orang sebagai kelompok kontrol dan 30 orang sebagai kelompok intervensi. Metode penelitian yang digunakan adalah quasi eksperiment dengan pendekatan pre post test control group dan menggunakan analisa uji t (paired t test) untuk mengukur kemandirian anak prasekolah sebelum dan sesudah dilakukan metode bermain peran  dan uji t-independen untuk melihat perbedaan kelompok intervensi dan kontrol.Hasil: Dari uji statistik didapatkan ada pengaruh metode bermain peran terhadap kemandirian anak prasekolah di TK Negeri Pembina Kecamatan Trimurjo Lampung Tengah Tahun 2012 dengan P Value 0,000 dengan tingkat kepercayaan 0,05 sehingga P Value < α (0,000 < 0,05).Kesimpulan: Hasil ini dapat menerapkan metode bermain peran dengan rancangan rencana kegiatan yang lebih disukai dan diminati anak. Kata Kunci     : Metode Bermain Peran dan Kemandirian Anak Prasekolah